Hubungan Antara Lama Bekerja dan Aspek Afektif Triage START pada Perawat Puskesmas: The Relationship Between Length of Work Experience and the Affective Aspect of START Triage Among Community Health Center Nurses - Suwardianto, Heru; Mahyuvi, Tata; Jaoquim, Pinto; Atta-Doku, John Foster; Ferede, Abebaw Jember (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Emergency situations and mass casualty incidents require nurses to make rapid, accurate, and evidence-based decisions, particularly in triage using the Simple Triage and Rapid Treatment (START) system. Nurses’ affective competence, including confidence, motivation, and emotional readiness, is crucial for effective triage. However, the relationship between length of service and affective competence remains underexplored in Indonesian community health centers. This cross-sectional study involved 27 nurses from 18 community health centers in Banten Province, Indonesia. A 15-item 4-point Likert questionnaire assessed affective competence in START triage, categorized into low, moderate, and high levels. Descriptive statistics and Pearson correlation analyzed the relationship between length of service and affective competence, with significance set at p < 0.05. Respondents were nearly evenly distributed by gender (48.1% male, 51.9% female) with a mean age of 37.07 ± 7.01 years and mean work experience of 14.81 ± 7.40 years. Most nurses (70.8%) demonstrated high affective competence, 29.2% moderate, and none low. Participants reported high confidence in understanding, explaining, and applying START, although some experienced difficulty in real-life scenarios. Correlation analysis indicated no significant relationship between length of service and affective competence (r = -0.053, p = 0.793). Nurses’ affective competence appears more influenced by training and practical experience than years of service. Structured training programs are essential to enhance affective competence in START triage, regardless of professional tenure.